1991
DOI: 10.1113/jphysiol.1991.sp018586
|View full text |Cite
|
Sign up to set email alerts
|

The two power limits conditioning step frequency in human running.

Abstract: SUMMARY1. At high running speeds, the step frequency becomes lower than the apparent natural frequency of the body's bouncing system. This is due to a relative increase of the vertical component of the muscular push and requires a greater power to maintain the motion of the centre of gravity, Wext. However, the reduction of the step frequency leads to a decrease of the power to accelerate the limbs relatively to the centre of gravity, Wint, and, possibly, of the total power Wtot -Wext + Wint -2. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 15 publications
3
81
0
3
Order By: Relevance
“…The results of previous studies have identified a number of biomechanical variables that relate to running economy, including stride length that is freely chosen (11,13,14,38,42,54), low vertical oscillation of body center of mass (13,54), and low peak ground reaction forces (54,55). In this study, we considered the basic biomechanical characteristics most often reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies have identified a number of biomechanical variables that relate to running economy, including stride length that is freely chosen (11,13,14,38,42,54), low vertical oscillation of body center of mass (13,54), and low peak ground reaction forces (54,55). In this study, we considered the basic biomechanical characteristics most often reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the freely chosen step frequency coincides with the frequency minimizing the step-average mechanical power at ~13 km h -1 ( Figure 14) [40]. At lower and higher speeds the freely chosen step frequency requires a step-average mechanical power greater than the minimal attainable with higher, respectively lower step frequencies ( Figure 14).…”
Section: Strategies Usedmentioning
confidence: 99%
“…The freely chosen step frequency is indicated on the abscissa by the closed arrow. Modified from [40]. Figure 13) and the push-average power (f o,push : open arrows in the right panels of Figure 13) are minimal.…”
Section: Difference Between Frequency Minimizing Mechanical Power Outmentioning
confidence: 99%
See 2 more Smart Citations